Five Islands, Port of Spain, Trinidad - (:unkn) unknown (Bonanza Smith Bros. and Co.,[Trinidad and Tobago], 2011)
The Five Islands are a group of actually six small islands lying west of Port of Spain in the Gulf of Paria. Also known as Las Cotorras, the islands are: Caledonia Island, Craig Island (Craig and Caledonia are joined by a man made causeway), Lenagan Island, Nelson Island, Pelican Island and Rock Island.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago; Paria, Gulf of (Venezuela and Trinidad and Tobago); Five Islands, The